Unusual association of brain hemorrhage and digestive tract occlusion: about two prenatal cases. Issue 12 (28th October 2016) - Garofalo, Giulia; Tecco, Laura; Van Rysselberge, Michel; Van Bogaert, Patrick; Mergan, Frederic; Cassart, Marie
Key Clinical Message: We report two prenatal cases of an exceptional association of digestive tract atresia or perforation with brain hemorrhage. This combination worsens the prognosis leading to termination of pregnancy in one case. We outline the importance of a careful fetal brain examination on imaging in cases of prenatal "acute" abdominal insults. Abstract : We report two prenatal cases of an exceptional association of digestive tract atresia or perforation with brain hemorrhage. This combination worsens the prognosis leading to termination of pregnancy in one case. We outline the importance of a careful fetal brain examination on imaging in cases of prenatal "acute" abdominal insults.